A Coupled Smoothed Finite Element-Boundary Element Method for Structural-Acoustic Analysis of Shell - TIAN, Wanyi; YAO, Lingyun; LI, Li (Archives of Acoustics, 2017)
Nowadays, the finite element method (FEM) – boundary element method (BEM) is used to predict the performance of structural-acoustic problem, i.e. the frequency response analysis, modal analysis. The accuracy of conventional FEM/BEM for structural-acoustic problems strongly depends on the size of the mesh, element quality, etc. As element size gets greater and distortion gets severer, the deviation of high frequency problem is also clear. In order to improve the accuracy of structural-acoustic problem, a smoothed finite-element/boundary-element coupling procedure (SFEM/BEM) is extended to analyze the structural-acoustic problem consisting of a shell structure interacting with the cavity in this paper, in which the SFEM and boundary element method (BEM) models are used to simulate the structure and the fluid, respectively. The governing equations of the structural-acoustic problems are establishedby coupling the SFEM for the structure and the BEM for the fluid. The solutions of SFEM are often found to be much more accurate than those of the FEM model. Based on its attractive features, it was decided in the present work to extend SFEM further for use in structural-acoustic analysis by coupling it with BEM, the present SFEM/BEM is implemented to predict the vehicle structure-acoustic frequency response analysis, and two numerical experiments results show that the present method can provide more accurate results compared with the standard FEM/BEM using the same mesh. It indicates that the present SFEM/BEM can be widely applied to solving many engineering noise, vibration and harshness (NVH) problems with more accurate solutions.